2013
DOI: 10.1172/jci65764
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenylcysteine carboxylmethyltransferase deficiency exacerbates KRAS-driven pancreatic neoplasia via Notch suppression

Abstract: RAS is the most frequently mutated oncogene in human cancers. Despite decades of effort, anti-RAS therapies have remained elusive. Isoprenylcysteine carboxylmethyltransferase (ICMT) methylates RAS and other CaaX-containing proteins, but its potential as a target for cancer therapy has not been fully evaluated. We crossed a Pdx1-Cre;LSL-Kras G12D mouse, which is a model of pancreatic ductal adenocarcinoma (PDA), with a mouse harboring a floxed allele of Icmt. Surprisingly, we found that ICMT deficiency dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 63 publications
(89 reference statements)
2
42
0
Order By: Relevance
“…So, we inferred that OS pathogenesis may be related to wnt and Myc pathway abnormality and the genes in these functional nodes, such This result agreed with the findings of previous studies: TGFB1 involves in the osteoblastic changes in bone metastasis [19], and the differentiation of cancer cells to cancer stem cells in OS [20]; FLT3 could inhibit proliferation and promote cell death in OS cell lines [21]. Moreover, the metastatic and non-metastatic OS are closely related to KDM1A gene down-regulation, which is an evidence supporting the points that KDM1A is a therapeutic target for OS [22] and KRAS is a underlying target gene for OS treatment [23].…”
Section: Discussionsupporting
confidence: 67%
“…So, we inferred that OS pathogenesis may be related to wnt and Myc pathway abnormality and the genes in these functional nodes, such This result agreed with the findings of previous studies: TGFB1 involves in the osteoblastic changes in bone metastasis [19], and the differentiation of cancer cells to cancer stem cells in OS [20]; FLT3 could inhibit proliferation and promote cell death in OS cell lines [21]. Moreover, the metastatic and non-metastatic OS are closely related to KDM1A gene down-regulation, which is an evidence supporting the points that KDM1A is a therapeutic target for OS [22] and KRAS is a underlying target gene for OS treatment [23].…”
Section: Discussionsupporting
confidence: 67%
“…In a mouse model of K-Ras-induced myeloproliferative disease, loss of ICMT ameliorated tumor growth, whereas loss of RCE1 accelerated it (50,51). More recently, it was found that ICMT deficiency enhanced K-Ras-driven pancreatic cancer development (52). A logical explanation for these different consequences for Ras-driven oncogenesis is that ablation of RCE1 or ICMT expression alters the function of other CAAX-terminating prenylated proteins, including small GTPases such as Ral and Rac that function downstream of Ras effector signaling, or of Ras family proteins that can act as tumor suppressors (53).…”
Section: Discussionmentioning
confidence: 99%
“…3,6 On the other hand, deficiency of isoprenylcysteine carboxylmethyltransferase, which methylates Ras and is considered a target for cancer therapy, surprisingly exacerbated Kras-driven PDAC owing to suppression of Notch1. 7 Therefore, roles of individual Notch receptors and their regulation in PDAC remain to be defined.…”
Section: Introductionmentioning
confidence: 99%